Proceedings of the 3rd ACM SIGSPATIAL International Workshop on Security and Privacy in GIS and LBS 2010
DOI: 10.1145/1868470.1868479
|View full text |Cite
|
Sign up to set email alerts
|

Show me how you move and I will tell you who you are

Abstract: International audienceDue to the emergence of geolocated applications, more and more mobility traces are generated on a daily basis and collected in the form of geolocated datasets. If an unauthorized entity can access this data, it can used it to infer personal information about the individuals whose movements are contained within these datasets, such as learning their home and place of work or even their social network, thus causing a privacy breach. In order to protect the privacy of individuals, a sanitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
138
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 21 publications
0
138
0
Order By: Relevance
“…Numerous privacy breaches have been proposed to illustrate how to breach the user privacy to obtain trajectory data [18,[22][23][24]. In this section, we briefly review the inference and linking attacks, anonymization techniques, adversary, and background knowledge of trajectory data analysis.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous privacy breaches have been proposed to illustrate how to breach the user privacy to obtain trajectory data [18,[22][23][24]. In this section, we briefly review the inference and linking attacks, anonymization techniques, adversary, and background knowledge of trajectory data analysis.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This knowledge could be workplaces, home addresses, social networks, places of interest, mobility patterns, physical conditions, and political views. For instance, recent studies [18,25,26] show that the movement patterns can be predicted from visited places. In the study by Song et al [26], the authors analysed 50,000 users' anonymized trajectories obtained from a mobile phone company, and the results show that 93% of the data could be used for mobility prediction.…”
Section: Inference and Linking Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, user's exposed locations can be transformed into his exposed POIs where he queries LBSs [35]. Indeed, it has been demonstrated that inference of POIs leads to a sever privacy breach [36].…”
Section: Motivation and Basic Ideas Inmentioning
confidence: 99%
“…Gambs et al [7], [8] proposed a Mobility Markov-chain Model (MMC) to incorporate the n previous visited locations and its extension coined as n-MMC to predict next possible [9] conducted another evaluation of n-MMC in the indoor context and the prediction rate is only up to 49% when n=2. Two main realistic context differences lead to n-MMC cannot reach the similar prediction accuracy in indoor context as the one in outdoor context.…”
Section: Related Workmentioning
confidence: 99%